1995
DOI: 10.1364/ao.34.004486
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol features retrieved from solar aureole data: a simulation study concerning a turbid atmosphere

Abstract: The characteristics of the solar aureole were evaluated for several cases of a turbid atmosphere in the 3° ≤θ≤30° interval of scattering angles; for each case, the features of the aerosol were retrieved from the simulated aureole data. Computations were carried out with a recently set up radiative transfer code that uses the approximated delta-M method, corrected further for the 1st and 2nd scattering orders. Results showed that the software tested can work out both the direct and the inverse aureole problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 26 publications
0
23
0
1
Order By: Relevance
“…The difference between retrieved tð0:5Þ (and a) is less than 0.01 (and 0.06). Tonna et al (1995) concluded that the sky radiometer is quite reliable in the field. Å ngström (1964) discussed the relationship between the size distribution of aerosols and the wavelength dependency of optical thickness.…”
Section: Instrumentationmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference between retrieved tð0:5Þ (and a) is less than 0.01 (and 0.06). Tonna et al (1995) concluded that the sky radiometer is quite reliable in the field. Å ngström (1964) discussed the relationship between the size distribution of aerosols and the wavelength dependency of optical thickness.…”
Section: Instrumentationmentioning
confidence: 99%
“…Measurements were made every 10 minutes at Sapporo and every 15 minutes at other sites. The scanning method is described in detail in Tonna et al (1995). As shown in Fig.…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement interval is typically 10 min. More details about the instrument and working principle can be found in papers by Nakajima et al (1996) and Tonna et al (1995). The sky radiometer commenced running in 2002 and continued measurements till early 2005.…”
Section: Instrument and Sitementioning
confidence: 99%
“…Surface reflection increases radiance both in the solar principal plane (SPP) and also in almucantar (ALM). Tonna et al [1995] also report the sensitivity of radiance to the surface albedo. Uncertainty of aerosol optical properties derived from radiance measurements is increased whenever the surface optical properties are not known.…”
Section: Introductionmentioning
confidence: 99%